Beyond the Heisenberg model: Anisotropic exchange interaction between a Cu-tetraazaporphyrin monolayer and Fe3O4(100) - SHVETS, IGOR (My University, 2013)
The exchange coupling of a single spin localized at the central ion of Cu-tetraazaporphyrin on a magnetite(100) surface has been studied using x-ray magnetic circular dichroism (XMCD). Sum rule analysis of the XMCD spectra results in Cu spin and orbital magnetic moments as a function of the applied external field at low temperatures (20 K). The exchange coupling is positive for magnetization direction perpendicular to the surface (ferromagnetic) while it is negative for in-plane magnetization direction (antiferromagnetic). We attribute the anisotropy of the Heisenberg exchange coupling to an orbitally dependent exchange Hamiltonian.
PUBLISHED
Keywords: in-plane magnetization; in-plane magnetization